Exploring the Model of Contemporary Chinese Ethnic Musical Instrument Improvement Mechanisms: Based on Grounded Theory - Ma, Yidi; Chen, Yan (SAGE open, 2024)
Modern Chinese traditional instruments have also embarked on a path of learning from Western musicology. Most research on instrument improvement has focused solely on Western instruments and issues inherent to the instruments themselves. However, to explore further directions for the improvement of Chinese instruments and enhance the quality of instrument creation and performance, this paper employs grounded theory to construct a “Sound Performance—Subject Driving—Environmental Inducing” dynamic model (SSE) for the improvement of Chinese traditional instruments. This model analyzes the various factors and driving mechanisms influencing improvement. We found that sound optimization is the main force driving instrument improvement, exerting the greatest influence on the improvement process. In terms of external driving forces, professional knowledge and esthetic pursuit play a crucial role, forming a dynamic triangular relationship among instrument manufacturers, performers, and Chinese traditional music groups. The dynamic changes in instrument improvement, through this triangular interaction, are ultimately influenced by cultural recognition, social policy, and technological innovation.